TINJAUAN YURIDIS PERATURAN DAERAH LAMONGAN NO. 12 TAHUN 2010 MENGENAI PAJAK DAERAH ATAS PAJAK RESTORAN SEBAGAI UPAYA PENINGKATAN PENDAPATAN DAERAH LAMONGAN - Sholihan Sholihan; Zuli Kasmawanto; Ahmad Munir (LPPM UNISDA, 2017)
Restaurant taxes contribute significantly to local financial revenues. In an effort to increase revenue from the restaurant tax sector, Lamongan District Government implemented the